Kilka uwag historyka myśli politycznej o potrzebie badania napięć między tym, co uniwersalne, i tym, co partykularne (także narodowe) .......... 37 - Szlachta, Bogdan (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
SOME COMMENTS FROM A HISTORIAN OF POLITICAL THOUGHT ON THE NEED TO RESEARCH THE TENSIONS BETWEEN THE UNIVERSAL AND THE PARTICULAR (ALSO NATIONAL)One of the most interesting and important disputes waged by ethicists who do not limit themselves to the analysis of what individuals consider to be good, as well as by political philosophers in the field of political thought, touching on the issue of establishing or learning about the normative order, concerns the source in or outside the individual of what is good and what constitutes the normative order. This dispute, which also highlights the problematic nature of the positivist position in the face of the multiplicity of narratives, discourses and cultures, is to some extent rooted in the old dispute between republicans and liberals.